PEMANFAATAN LIMBAH KULIT UDANG SEBAGAI BAHAN BAKU PEMBUATAN MEMBRAN ULTRAFILTRASI - Kusumawati, Nita (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
Abstract This research was aimed to study the made of chitosan membrane. The chitosan membrane was made from industrial waste of prawn packing factory. The prawn husk was extracted to become chitin before it was then transformed to chitosan. In order to make a membrane, the chitosan was mixed with an acetic acid solution using magnetic stirrer. The mixed of chitosan and an acetic acid solution was doing for 24 hour to make sure the solution are homogenic. After that, chitosan solution was stored to glass plate 10x10 cm. The glass plate that have been with chitosan solution then dried for 48 hours. A Chitosan Membrane that have made was keeped with the plate until it used. Keywords: chitosan membrane, industrial waste